Helical Bilayer Nonbenzenoid Nanographene Bearing a [10]Helicene with Two Embedded Heptagons. Issue 4 (20th December 2022) - Yang, Lin; Ju, Yang‐Yang; Medel, Miguel A.; Fu, Yubin; Komber, Hartmut; Dmitrieva, Evgenia; Zhang, Jin‐Jiang; Obermann, Sebastian; Campaña, Araceli G.; Ma, Ji; Feng, Xinliang
Abstract: The precision synthesis of helical bilayer nanographenes (NGs) with new topology is of substantial interest because of their exotic physicochemical properties. However, helical bilayer NGs bearing non‐hexagonal rings remain synthetically challenging. Here we present the efficient synthesis of the first helical bilayer nonbenzenoid nanographene (HBNG1 ) from a tailor‐made azulene‐embedded precursor, which contains a novel [10]helicene backbone with two embedded heptagons. Single‐crystal X‐ray analysis reveals its highly twisted bilayer geometry with a record small interlayer distance of 3.2 Å among the reported helical bilayer NGs. Notably, the close interlayer distance between the two layers offers intramolecular through‐space conjugation as revealed by in situ spectroelectrochemistry studies together with DFT simulations. Furthermore, the chiroptical properties of the P/M enantiomers of HBNG1 are also evaluated by circular dichroism and circularly polarized luminescence. Abstract : A helical bilayer nonbenzenoid nanographene has been synthesized with a novel [10]helicene backbone bearing two heptagons. Single‐crystal X‐ray analysis revealed its highly twisted bilayer geometry with a small interlayer distance of 3.2 Å, in which the intramolecular through‐space conjugation between the two layers is determined. Furthermore, the chiroptical properties of the P / M enantiomers of this helical nanographene have also been evaluated.